PROFIL KEJADIAN PERNIKAHAN USIA DINI DI WILAYAH KERJA LUBUK GADANG KECAMATAN SANGIR - Nita Tri Putri; Nurul Amalina (Maternal Child Health Care, 2022)
The increase in early marriage in Sangir District in 2019 was 31 people, in 2020 38 people and in 2021 as many as 39 people. Early marriage has a psychological, health, and socio-economic impact on adolescents. The purpose of this study was to determine the profile of the incidence of early marriage in the working area of the Lubuk Gadang Health Center, Sangir District, South Solok Regency. The type of research used is quantitative analysis with analytical descriptive method with observational design. all teenagers who got married at an early age from January to December 2021 were 107 teenagers. Sampling technique with total sampling. The data used are primary data and secondary data. Analysis of research results was carried out univariately. The results showed that the age of married adolescents was 15-19 years where as many as 55 people (51.4%) were <21 years old at the time of marriage, 93 people (86.9%) were female, 48 people (44.9%) had education level, namely graduated from junior high school, 47 people (43.9%) have jobs as housewives, 100 people (93.5%) have low incomes and 63 people (58.9%) have low parental income, 55 people ( 51.4%) have legal marriage status, 42 people (39.3%) have sufficient and high knowledge about early marriage, 76 people (71%) have a negative perception. Based on the results of the study, it was concluded that there were many factors that led to early marriage, the income factor of parents being the most influencing factor for adolescents. So it is recommended for the working area of the Lubuk Gadang Health Center to be able to often provide health education about the impact of early marriage on adolescents. Keywords: Early Marriage, Knowledge, Adolescent Perceptions, Marital Status